Impacto de la era digital en la Comunicación Corporativa dentro de la Casa de la Cultura, Benjamín Carrión Núcleo de Bolívar, período enero-abril 2023 - Lumbi Peña, Nathaly Lisbeth (2024)
This study analyzes the fundamental principles of the digital era: the development of the Internet, the emergence of web generations and the importance of digital communication tools. The objective of the study is to examine how technology has affected corporate communication, with special emphasis on the Casa de la Cultura del núcleo Benjamín Carrión Bolívar. Through the digital era, virtual communication tools have constantly appeared, transforming to the convenience of organizations that manage a corporate margin, the interpersonal relationships that must be dealt with within the institutions have adapted to technology. In the digital era, social networks, websites, instant messaging, videoconferencing and other technologies have become increasingly important. In a similar vein, these platforms have helped the Casa de la Cultura, Benjamín Carrión Bolívar, with its corporate communication. Therefore, the objective of this study is to develop a Guide for the Use of Digital Communication Tools in the CCENB and to evaluate the effects and viability of the digital era in the corporate communication of the Casa de la Cultura, Benjamín Carrión núcleo de Bolívar.